Geographical Multicast Quality of Service Routing Protocol for Mobile Ad-Hoc Networks - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K. (Newswood Ltd., 2011)
Recently, the necessity of applications where many users have to interact in a close manner over mobile Ad-Hoc networks gains high popularity. Multicast communication is essential in this type of applications to reduce the overhead of group communication. For group-oriented multimedia applications Quality of Service (QoS) provision is a basic requirement, which makes an efficient QoS multicast routing protocol a very important issue. This paper proposes a location-based QoS multicast routing protocol via cooperation between Network and MAC layers. Along with this protocol, a location and group membership management scheme has been proposed. To further reduce the control overhead and bandwidth consumption, we apply clustering strategy by partitioning the network topology into hexagon cells. Thus, maintaining the network topology is limited to certain nodes. The performance of the proposed protocol is evaluated using GloMoSim simulation environment. Simulation results show that our approach provides high packet delivery ratio associated with low control overhead.